Development of an eicosapentaenoic acid production bioprocess using an indigenous microalgal isolate - Dickson, Darin (Centre for Bioprocess Engineering Research, 2015)
Eicosapentaenoic acid (EPA; 20:5) is an omega-3 polyunsaturated fatty acid of increasing interest as a nutraceutical. An indigenous microalgal isolate suitable for an EPA bioprocess was selected by screening monoalgal isolates from the Council for Scientific and Industrial Research (CSIR) micro-algal culture collection. A Cymbella diatom (A23.2) was selected for superior EPA production in both growth and stress conditions, using both fluorescent microscopy and flask studies. Studies investigated increasing biomass, improving EPA content, and optimising overall EPA productivity in a multi-stage bioprocess. Growth studies found self-regulatory systems in both phosphate and nitrate metabolism. These mechanisms were absent in silicate and bicarbonate consumption, prompting their optimisation in the bioprocess medium. Cultivation pH was found to have a statistically modelled optimal value of 7.2 and a light intensity at a low range of 60 – 70 ìmol.m-2.s-1 was found to be suitable. Nutrient and physicochemical parameters were assayed individually, and revealed cell productivities of between 2.0 x 108 to 3.0 x 108 cell.L-1.hr-1 in batch culture bioreactor studies. Further studies demonstrated the use of both nutrient stress and physicochemical stress to enhance EPA production. These results informed the choice of operating parameters for a proof of concept, multistage raceway-based EPA bioprocess, consisting of a single growth pond and three stress ponds linked in series. The growth phase EPA productivity data of 0.68 mg.L-1.day-1, was higher than that of the stress phase, supporting its classification as a growth-associated product. Further, the EPA productivity in the raceway was more than twice that of initial batch culture screening. Once experimental limitations are addressed, a re-design of the bioprocess can be undertaken by optimising growth phase residence time, medium flow-rate and partial/complete elimination of the stress phase. The EPA productivity of the diatom used in this work has the potential of reaching commercially viable values. The development of a commercial indigenous EPA producer has a dual impact, as it addresses various nutritional and medicinal market demands and improves the sustainability of the world’s fish stocks.